The Egyptian Item - Hinson, Benjamin (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
The author presents a proposed translation of the uncertain architectural term c d, found within the Chester Beatty love poems. It is argued to correlate with the archaeologically well-attested mechanism called a Stoßschlüssel, used for both barring and unlocking a door and thus acting as a combined lock and key.